A Wall or a Bridge : Examining the Impact on Sino-South Korean Relations through Cultural Diplomacy - Gong, Junkai; Votoupalová, Markéta; Garlick, Jeremy; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
K-pop and K-drama have become household names globally, with groups like BTS and Black Pink recognized in nearly every corner of the world. The widespread appeal of these cultural products underscores the remarkable success of Hallyu, as a force of cultural diplomacy. This thesis investigates the dual role of Hallyu in shaping Sino-South Korean relations, emphasizing its significance as a tool for fostering cultural exchange and enhancing South Korea's soft power. By leveraging cultural exports, South Korea has successfully projected its cultural identity and values, strengthening its national image and forging closer ties with audiences in China and beyond. Meanwhile, this thesis also examines the vulnerabilities of Hallyu, particularly in the face of geopolitical tensions such as the THAAD crisis, which led to significant restrictions on Korean cultural imports in China. The study analyzes Hallyu’s historical development, its mechanisms of globalization through digital platforms and fan communities, and its influence on regional and global perceptions of South Korea. Using qualitative methods and case studies, this research highlights the complexities of Hallyu as both a cultural bridge and a potential flashpoint in Sino-South Korean relations. The findings demonstrate that while Hallyu has been an effective tool for cultural diplomacy, its success is contingent upon political and economic stability. This thesis offers insights into the dynamic relationship between culture and politics, providing recommendations for sustaining the impact of cultural diplomacy in an increasingly polarized geopolitical landscape. By examining the interplay of culture, politics, and international relations, this study contributes to a deeper understanding of the potential and limitations of soft power in a globalized world.
Vedoucí práce: Markéta Votoupalová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses